Historical Medical Archives and Libraries. : The case of Historical Archive of Eginitio Hospital - Katsigianni, Penelope (Journal of Integrated Information Management, 2025)
Purpose - One of the goals of modern nursing institutions should be the preservation and promotion of their historical archives, as they represent the primary source of local medical history and society. Medical archives have historical importance and can document the knowledge, the beliefs of healthcare professionals, the development of health and medicine. The purpose of this article is to highlight the importance of the preservation of historical medical archives and the leading role of the hospital library to their management and promotion, as a golden value-added service, according to the MLA Standards of Practice for Hospital Libraries and Librarians, 2022. Design/methodology/approach - This article will present the challenges that may arise during the establishment and management of a historical medical archive. It will also cover the digitization process of a historical medical archive and the importance of data protection, particularly patient privacy and security. The case of the Historical Archive of Eginitio Hospital and the management by its library will be presented. It is an ambitious and challenging project in progress that will preserve the history of the nursing institution, the revolution of neurology and psychiatry and the broader societal impact of these fields. Findings - The hospital library, by undertaking the management of the institution’s historical archive, offers an added value service, which enhances its profile and visibility and highlights it as a place of historical information and acquires a new demanding educational role. As a project, it is not easy because it requires knowledge of archive maintenance and organization, promotion and visibility of the archive to the researchers and to the public, which consequently demands sufficient staff and significant funding. Originality/value - This paper introduces, for the first time, the issue of managing and organization of a historical hospital archive by its library in Greece.